Preface - A. Marcela Printista; Carlos García Garino (CLEI Electronic Journal, 2014)
This Special Issue of CLEI Electronic Journal presents the invited contributions selected from the best evaluated papers presented in VI HPCLatAm 2013. These communications that have been conveniently extended and properly evaluated. In this way the selected papers are a valuable contributions to the development of high performance computing in Latin America and summarizes the state of the art of HPC in our region.